2015
DOI: 10.1007/s00062-015-0399-6
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Mean Transit Time Maximization is Associated with Neurological Outcome After Subarachnoid Hemorrhage

Abstract: The current findings suggest a presumably higher vulnerability of the brain to early microcirculatory impairments after aSAH and highlight that timing of MTT elevations could be considered for the identification of patients at increased risk for poor neurological outcome due to DCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Some studies have indicated that cerebral circulation time (CCT) can reflect the status of microcirculatory impairment. [17][18][19] Several studies using computed tomography perfusion have examined the relationship between DCI and indicators related to the CCT, such as the mean transit time (MTT) and the time to peak (TTP), but they did not reach a definite conclusion about their relationship to DCI, and a consensus among studies could therefore not be reached. [20][21][22][23][24][25][26][27][28][29][30][31][32] Digital subtraction angiography (DSA) is recognized as the most reliable method for the evaluation of CCT and aVS.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that cerebral circulation time (CCT) can reflect the status of microcirculatory impairment. [17][18][19] Several studies using computed tomography perfusion have examined the relationship between DCI and indicators related to the CCT, such as the mean transit time (MTT) and the time to peak (TTP), but they did not reach a definite conclusion about their relationship to DCI, and a consensus among studies could therefore not be reached. [20][21][22][23][24][25][26][27][28][29][30][31][32] Digital subtraction angiography (DSA) is recognized as the most reliable method for the evaluation of CCT and aVS.…”
Section: Introductionmentioning
confidence: 99%
“…However, PBV only provides cerebral blood volume values at present but lacks perfusion parameters of CBF, MTT, and TTP. The evaluation of patients who have no obvious CBV abnormalities in the early stage, with only prolonged MTT and slightly decreased CBF, may be inaccurate ( 48 ). Improved PBV technology that can calculate more perfusion parameters in the future may help in a more comprehensive and accurate evaluation of the brain perfusion status ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in concordance with the cerebral pathological changes after aneurysmal SAH. CBF could maintain stability in patients with intact autonomic regulation (45)(46)(47), but increased intracranial pressure (ICP) and decreased CBF after aneurysmal SAH lead to congestive changes in brain tissue manifested by dilated cerebral arterioles and increased CBV in patients with impaired autonomic regulation (11,48,49). The blood supply of the parietal ROIs that we selected was covered by the middle cerebral artery, which responded immediately after hemorrhage and manifested as cerebral congestion, resulting in increased PBV in the parietal ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…The few published studies included mostly early CT perfusion evaluations, before the vasospasm time window. One recent study found that the earliest the perfusion changes occur, the higher likelihood of poor outcome in patients with DCI (76). From all perfusion parameters, MTT seems to be the most significant regarding outcome prediction.…”
Section: Imaging Predictors Of Clinical Outcomementioning
confidence: 99%